Evidence-Based School Development in Changing Demographic Contexts - Ylimaki, Rose M.; Brunderman, Lynnette A. (Studies in Educational Leadership, 2022)
This Open Access book features a school development model (Arizona Initiative for Leadership Development and Research - AZiLDR) that offers a roadmap for schools to navigate the complexities of continuous school development. Filled with processes that balance evidence-based values with democratic, culturally responsive values, this book offers strategies to mediate the tensions and to address school culture, context and values, leadership capacity, using data as a source of reflection, curricular and pedagogical activity, and strengths-based approaches to meeting the needs of culturally diverse students. You will find: · - Active, reflective activities · - Case studies illustrating each concept · - The research base supporting each concept · - Descriptions of processes from other contexts (South Carolina, Germany, Australia, Sweden) · - Thoughts about next steps for contextually sensitive and multi-level school development · - Suggestions for cross-national dialogue and research within the Zone of Uncertainty Use this ideal source to guide school leadership teams in creating productive schools that continually grow!